Возможность создания синхронных выключателей на базе современных вакуумных камер - Гилёв, Александр Александрович (НТУ "ХПИ", 2005)
В статье рассматривается возможность создания вакуумных выключателей с учетом особенностей серийно выпускаемых вакуумных дугогасительных камер; предлагаются пути решения возникающих при этом проблем.

In the article, a possibility of developing vacuum breakers allowing for features of commercial vacuum extinguishing chamber is considered,and ways of solving concurrent problems are suggested.
Possibility of development of synchronous vacuum circuit-breakers based on state-of-theart vacuum chambers
Keywords: вакуумные дугогасительные камеры; электрические цепи; вакуумные камеры; вакуумные выключатели; vacuum extinguishing chamber; fast response; synchronous vacuum circuit-breaker